Secondary Metabolites Released by the Rhizosphere Bacteria Arthrobacter Oxydans and Kocuria Rosea Enhance Plant Availability and Soil–Plant Transfer of Germanium (Ge) and Rare Earth Elements (Rees) - Levican-Jaque, G (Elsevier Ltd, 2021)
Here, we explore effects of metallophore-producing rhizobacteria on the plant availability of germanium (Ge) and rare earth elements (REEs). Five isolates of the four species Rhodococcus erythropolis, Arthrobacter oxydans, Kocuria rosea and Chryseobacterium koreense were characterized regarding their production of element-chelators using genome-mining, LC-MS/MS analysis and solid CAS-assay. Additionally, a soil elution experiment was conducted in order to identify isolates that increase solubility of Ge and REEs in soil solution. A. oxydans ATW2 and K. rosea ATW4 released desferrioxamine-, bacillibactin- and surfactin-like compounds that mobilized Ge and REEs as well as P, Fe, Si and Ca in soil. Subsequently, oat, rapeseed and reed canary grass were cultivated on soil and sand and treated with cells and iron depleted culture supernatants of A. oxydans ATW2 and K. rosea ATW4. Inoculation increased plant yield and shoot phosphorus (P), manganese (Mn), Ge and REE concentrations. However, effects of the inoculation varied substantially between the growth substrates and plant species. On sand, A. oxydans ATW2 increased accumulation of REEs in all plant species and root–shoot translocation in rapeseed, while K. rosea ATW4 enhanced REE accumulation in rapeseed only, without effects on other plant species. Sand-cultured oat plants showed increased Ge accumulation and root–shoot translocation in presence of A. oxydans ATW2 cells and K. rosea ATW4 supernatant; however, there was no effect on other plant species, irrespective the growth substrate used. In contrast, soil-cultured rapeseed showed enhanced REE accumulation in presence of cells of A. oxydans ATW2 while there were no effects on other plant species and Ge. The processes involved are not yet fully understood. Nevertheless, we demonstrated that chemical microbe–soil–plant relationships influence plant availability of nutrients together with Ge and REEs, which has major implications on our understanding of biogeochemical element cycling and development of sustainable bioremediation and biomining technologies. © 2021 Elsevier Ltd